2014
DOI: 10.1016/j.jtcvs.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of exhaled carbonyl compounds distinguishes benign from malignant pulmonary disease

Abstract: Analysis of specific exhaled carbonyls can differentiate early lung cancer from benign pulmonary disease. Breath analysis was more specific than PET for a lung cancer diagnosis. Judicious use of these data may expedite the care of patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…Additional advantages of the current study include benchmarking of the simpler models with established statistical / machine-learning methods and optimization of cut-points for both individual VOCs and the number of elevated VOCs for determining whether a patient has lung cancer. It should also be noted that the carbonyl VOCs were equally effective in separating lung cancer cases from both smoking and non-smoking controls, in agreement with what we previously observed [24][25]. A limitation of the current work is that we selected the six VOCs for our simple model based on the best performing classifiers in the test data.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Additional advantages of the current study include benchmarking of the simpler models with established statistical / machine-learning methods and optimization of cut-points for both individual VOCs and the number of elevated VOCs for determining whether a patient has lung cancer. It should also be noted that the carbonyl VOCs were equally effective in separating lung cancer cases from both smoking and non-smoking controls, in agreement with what we previously observed [24][25]. A limitation of the current work is that we selected the six VOCs for our simple model based on the best performing classifiers in the test data.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous work identified four lung cancer markers C 4 H 8 O, 4-HHE, C 4 H 8 O 2 , and C 2 H 4 O 2 [24] and a diagnostic method based on counting the number of elevated these four markers was developed [25]. In this study, two additional markers 4-HNE and C 5 H 10 O were identified by the statistical classification models.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The assignment can be based on the functional group and the combined 1 H and 15 N chemical shifts [33,34]. Other CS probes have been developed by us that select for functional groups including thiols [35] and carbonyls (aldehydes and ketones) [36,37]. The resulting adducts in biological extracts are optimized for both MS analysis, and 15 N edited 1 H NMR analysis that makes use of long range 2 and 3-bond couplings [31].…”
Section: Nmr Is a Powerful Tool For Metabolite Identification And mentioning
confidence: 99%
“…The stability of real breath VOCs adsorbed on sorbents (Tenax TA and carbograph) in tube samples has recently been studied. [132][133]135 The objective of this study is to investigate the stabilities of breath VOCs in Tedlar have been reported as lung cancer biomarkers in exhaled breath. 116-117, 134,136 In this work, a silicon microreactor approach was used to capture trace carbonyl compounds in exhaled…”
Section: Introductionmentioning
confidence: 99%